Business Intelligence a supporto del GIS: ultime novità dal mondo GFOSS - D'Ovidio, Fabio (GEOmedia, 2009)
GeoBI (GeoSpatial Business Intelligence) open source project GeoBI (GeoSpatial Business Intelligence), a new open source project coming from Italy, look at the Geographic Information Systems (GIS) from a different point of view because it proposes to manage the alphanumeric component of cartographic data through Business Intelligence tools. This implies multidimensional webGIS usage in order to display charts, dials and diagrams on the map and spatially navigate OLAP cubes.